Experiential constructions in Latin - Fedriani, Chiara (Brill's studies in historical linguistics., 2014)
This book offers a corpus-based synchronic and diachronic investigation of Experiential constructions in Latin, focusing on patterns of variation and change in argument realization and non-canonical case-marking and providing insights in the domain of diachronic verbal syntax and semantics.